2021
DOI: 10.1016/j.heliyon.2021.e07569
|View full text |Cite
|
Sign up to set email alerts
|

Food, fields and forage: A socio-ecological account of cultural transitions among the Gaddis of Himachal Pradesh in India

Abstract: Traditional food systems of many ethnic communities in India directly depend on their symbiotic relationship with the surrounding natural resources and the local socio-ecological and cultural dynamics. However, in the light of development activities resulting in drastic socio-ecological changes, these communities are oftentimes found stranded with over-simplified and unsustainable food systems. Using an ethnographic methodology, we present the case of Gaddis – an agro-pastoral community of Himachal Pradesh in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…The majority of the research were carried out in the Himalayan region viz. in India [36,21,25,28,[32][33][34][35], Nepal [13,20], India and Nepal [22], China [15,16], Pakistan [14], Bhutan [23], Myanmar [24], Canada [26,27], Spain [17], Europe [29], Portland [19], Mexico [30], Joint research in Sweden, US, UK, and Japan [18], Nigeria [31], as shown in Table 1. Studies incorporated for the systematic analysis were based on the traditional community's traditional eating practices and the impact of climate change on indigenous people.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the research were carried out in the Himalayan region viz. in India [36,21,25,28,[32][33][34][35], Nepal [13,20], India and Nepal [22], China [15,16], Pakistan [14], Bhutan [23], Myanmar [24], Canada [26,27], Spain [17], Europe [29], Portland [19], Mexico [30], Joint research in Sweden, US, UK, and Japan [18], Nigeria [31], as shown in Table 1. Studies incorporated for the systematic analysis were based on the traditional community's traditional eating practices and the impact of climate change on indigenous people.…”
Section: Resultsmentioning
confidence: 99%
“…Further, in a traditional society, dietary habits depend on the familiarity and naturalness of food [29], customary norms [30], and taboos in indigenous communities [31]. Thus, the socio-cultural norms and beliefs system is imperative for environmentally sustainable practice [28,32,33].…”
Section: Table 1 the Findingsmentioning
confidence: 99%
“…It is clear from the above situation that hiring a puhal not only is restricted to the elite herd owners but also is emerging as a necessity to continue transhumant pastoralism amidst the external challenges that are either the consequences of shifts in agrarian practices of the region or are policy driven (Ramprasad et al 2020). It is observed that the settled Gaddi population located the region is increasingly shifting to crop cultivation, mainly in their winter homes at Kangra and to horticulture at their villages in Bharmour (Malhotra et al 2021). A duality in the residence and livelihood practices thus plays an important role in determining the labour dynamics within Gaddi pastoralism.…”
Section: Puhals: Hired Herding Practices In Gaddi Pastoralismmentioning
confidence: 99%
“…Along with that, it involves prolonged isolation periods away from home and in the wild that demands high levels of mental and emotional stability. The demanding nature of this job, apart from the external pressures, also includes dealing with the changing weather conditions, negotiating with the settled communities and traders, medical emergencies and natural calamities makes it a tough livelihood choice, more so, in the current times when the development discourse of modernity and urban lifestyle promoting sedentarisation is heavily imposed by the authorities and gradually internalised by the community members (John and Badoni 2013;Malhotra et al 2021). Following this, a shift in the aspirations of the educated youth of the community who are increasingly shunning the migratory lifestyle that is perceived to be devoid of a sense of stability, personal hygiene, social dignity and public status is creating a huge void in terms of labour.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, it is assumed that all transitions follow similar principles and are guided by the same mechanisms. Thus, for example, transformations in agriculture [4], wastewater infrastructure [5], transportation [6,7] or food [8][9][10] are investigated and can be conceptualized in the same way. Such transitions are also sometimes called sustainability transitions and involve changes in socio-technical systems.…”
Section: Literature Reviewmentioning
confidence: 99%